A double-sided radiating flat-panel X-ray source using ZnO nanowire field emitters. (October 2017) - Chen, Daokun; Xu, Yuan; Zhang, Guofu; Zhang, Zhipeng; She, Juncong; Deng, Shaozhi; Xu, Ningsheng; Chen, Jun
Abstract: A double-sided radiating flat-panel X-ray source device has been developed. The device has a diode configuration composed of an anode target of a tungsten thin film and field-emitter arrays of ZnO nanowires prepared on glass substrates. The X-ray radiation comes from both transmission and reflection of X-rays induced by electron bombardment. When operated at 24 kV with an anode current of 3.16 mA, radiation dose rates of ∼200 mGy/min and ∼210 mGy/min were recorded positioning at 4 cm away from the front and back sides of the vacuum-sealed flat-panel X-ray source, respectively. Clear X-ray images with high contrast were taken by the radiation from both sides of the device. The reported device has great potential in making compact X-ray radiography and irradiation systems. Highlights: A vacuum-sealed double-sided radiating flat-panel X-ray source device using ZnO nanowire field emitters. Good field emission properties from ZnO nanowires and similar X-ray radiation from both sides of the device. Potential applications of the device in compact and portable X-ray radiography and irradiation systems.